On the true photoreactivity order of {001}, {010}, and {101} facets of anatase TiO2 crystals - Pan, Jian; Liu, G.; Lu, G.; Cheng, H. (2011)
Contrary to conventional understanding, clean anatase {001} facets exhibit lower photoreactivity than {101} facets. Furthermore, the {010} facets showed the highest photocatalytic reactivity in generating OH radicals and hydrogen evolution. This behavior was revealed by studies on crystals grown hydrothermally to have a predominance of {001}, {101}, or {010} facets (left to right in picture(a) and (b)-(d), respectively). © 2011 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim.